2022
DOI: 10.2106/jbjs.21.00727
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Delayed Hospital Admission and Surgical Treatment of Open Tibial Fractures in Tanzania

Abstract: Background: Open fractures, especially of the tibia, require prompt intervention to achieve optimal patient outcomes.While open tibial shaft fractures are common injuries in low-and middle-income countries (LMICs), there is a dearth of literature examining delays to surgery for these injuries in low-resource settings. This study investigated risk factors for delayed management of open tibial fractures in Tanzania. Methods:We conducted an ad hoc analysis of adult patients enrolled in a prospective observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Similarly, prior studies of trauma care delays in Rwanda and Tanzania have found that men are over-represented in comparison to women when examining delayed fracture care and delayed initial presentation after injury. 17 , 18 As such, men may be a population to focus on when implementing interventions to help patients receive definitive trauma care.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, prior studies of trauma care delays in Rwanda and Tanzania have found that men are over-represented in comparison to women when examining delayed fracture care and delayed initial presentation after injury. 17 , 18 As such, men may be a population to focus on when implementing interventions to help patients receive definitive trauma care.…”
Section: Discussionmentioning
confidence: 99%
“…Another major risk is that the operation of the center will foster long-term dependence upon the center for provision of select pediatric surgical procedures and thereby negatively impact efforts to develop these resources in country. The preceding paragraphs illustrate our efforts to ameliorate this outcome, but realistically access to such care is fundamentally an economic problem, not likely to be solved in the short term 14…”
Section: Discussionmentioning
confidence: 99%